Pengaruh Aktivitas Pemasaran Media Sosial terhadap Niat Pembelian pada Mahasiswa : Peran Brand Equity dan Social Brand Engagement, study kasus produk Kahf - Muhammad Nasyith Muharram; Agus Abdurrahman (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study provides a new perspective on the influence of social media marketing activities (SMMA) on the purchase intention of students towards the Kahf brand. The use of social media has truly increased massively, and this has led many companies to change the way they engage their brands with consumers. This phenomenon creates a need for this research to further investigate the influence of Social Media Marketing Activities (SMMA) on social brand engagement (SBE), brand equity (BAQ), and purchase intention (PIN). Therefore, the aim of this study is to explore the impact of SMMA on students' purchase intentions regarding the Kahf brand, considering brand equity and social brand engagement. This research uses the SOR (Stimulus Organism Response) theory as the foundation of the study. This research uses a quantitative method with 144 respondents, employing Roscoe's formula and purposive sampling technique. The data in this study was obtained by having respondents fill out a questionnaire. There are 20 questions that respondents must answer through Google Forms. The researcher analyzes the results of the discriminant validity using the Fornell-Larcker Criterion. This research aims to determine the impact of social media marketing activities (SMMA) and purchase intention on the products offered by the Kahf brand. The survey results will be analyzed using descriptive statistics, employing PLS-SEM version 4.0 and SPSS to test the quantitative data. The results of this study indicate that social media marketing activities have a positive and significant impact on purchase intention, while brand equity and social engagement do not have a positive and significant effect on purchase intention. The findings suggest that the effectiveness of marketing is achieved through social media marketing activities that positively and significantly influence respondents' purchase intentions.